Economic burden of public health care and hospitalisation associated with COVID-19 in China. (February 2022) - An, X.; Xiao, L.; Yang, X.; Tang, X.; Lai, F.; Liang, Xiao-Hua
Abstract: Objectives: This study aimed to evaluate the socio-economic burden imposed on the Chinese healthcare system during the coronavirus disease 2019 (COVID-19) pandemic. Study design: A cross-sectional study was used to investigate how COVID-19 impacted health and medical costs in China. Data were derived from a subdivision of the Centers for Disease control and Prevention of China. Methods: We prospectively collected information from the Centers for Disease Control and Prevention and the designated hospitals to determine the cost of public health care and hospitalisation due to COVID-19. We estimated the resource use and direct medical costs associated with public health. Results: The average costs, per case, for specimen collection and nucleic acid testing (NAT [specifically, polymerase chain reaction PCR]) in low-risk populations were 29.49 and 53.44, respectively; however, the average cost of NAT in high-risk populations was 297.94 per capita. The average costs per 1000 population for epidemiological surveys, disinfectant, health education and centralised isolation were 49.54, 247.01, 90.22 and 543.72, respectively. A single hospitalisation for COVID-19 in China cost a median of 2158.06 (1961.13-2325.65) in direct medical costs incurred only during hospitalisation, whereas the total costs associated with hospitalisation of patients with COVID-19 were estimated to have reached nearly 373.20 million in China as of 20, May, 2020. The cost of public health care associated with COVID-19 as of 20, May, 2020 (6.83 billion) was 18.31 times that of hospitalisation. Conclusions: This study highlights the magnitude of resources needed to treat patients with COVID-19 and control the COVID-19 pandemic. Public health measures implemented by the Chinese government have been valuable in reducing the infection rate and may be cost-effective ways to control emerging infectious diseases.